2011
DOI: 10.1155/2011/541592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar on Earthworm Populations: A Review

Abstract: Despite the overwhelming importance of earthworm activity in the soil system, there are a limited number of studies that have examined the impact resulting from biochar addition to soil. Biochar is part of the black carbon continuum of chemothermal converted biomass. This review summarizes existing data pertaining to earthworms where biochar and other black carbon substances, including slash-and-burn charcoals and wood ash, have been applied. After analyzing existing studies on black carbon, we identified that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Macrofaunal activity was evident at the field plots, in particular as visible surface earthworm activity and castings. However, a macrofaunal sampling established that earthworm abundance was not significantly different at the time of litterbag placement (Weyers and Spokas, 2011). This would be in agreement with other studies illustrating shortterm impacts on macrofaunal activity observed in short-term laboratory studies (i.e., months) Marks et al, 2014), but these short-term effects are not persistent in the field .…”
Section: Discussionsupporting
confidence: 89%
“…Macrofaunal activity was evident at the field plots, in particular as visible surface earthworm activity and castings. However, a macrofaunal sampling established that earthworm abundance was not significantly different at the time of litterbag placement (Weyers and Spokas, 2011). This would be in agreement with other studies illustrating shortterm impacts on macrofaunal activity observed in short-term laboratory studies (i.e., months) Marks et al, 2014), but these short-term effects are not persistent in the field .…”
Section: Discussionsupporting
confidence: 89%
“…Seemingly, the main impact caused by biochar on earthworms is due to pH, which can change responses according to the biochar application time (Weyers and Spokas, 2011).…”
Section: Standard Methods To Qualify Biocharmentioning
confidence: 99%
“…Nevertheless, the harmful materials released from pyrolyzed BC unintentionally may inhibit the soil organisms (Lehmann et al, 2011;Weyers and Spokas, 2011). Pyrolyzed BCs contain toxic metal(loid)s, PAHs, and dioxins with various isomers, which are associated with oxidative stress through accumulation of reactive oxygen stress (ROS) in cellular tissues (Stegeman and Lech, 1991;Lopez et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…Greater concentrations of 8-OHdG were observed by Li et al (2011) in soil amended with BC produced from woodchips at 550℃ than 300℃. The BCs pyrolyzed over 500℃ contain high concentrations of trace metal(loid)s, which are known to cause oxidative stress in earthworms (Weyers and Spokas, 2011).…”
Section: Enzyme Activity Measurementsmentioning
confidence: 99%